2015
DOI: 10.1037/cou0000110
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of clinical supervision in the Republic of Ireland and the United States.

Abstract: We replicated Son, Ellis, and Yoo (2013) and extended Ellis et al.'s (2014) taxonomy of harmful and inadequate supervision by providing and testing cross-national comparative descriptive data about clinical supervision practices in the Republic of Ireland versus the United States. Participants were 149 Republic of Ireland and 151 U.S. mental health supervisees currently receiving clinical supervision. The results suggested that characteristics of supervision in the Republic of Ireland and United States evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 23 publications
(58 reference statements)
3
35
0
2
Order By: Relevance
“…Ellis et al () found that 36% of their sample ( N = 363) were currently receiving harmful supervision. Similar findings have been reported in other studies, where prevalence rates vary between 20% and 40% (Bang & Goodyear, ; Ellis, ; Ellis, Creaner, Hutman, & Timulak, ; Hendricks & Cartwright, ; Nelson & Friedlander, ; Ramos‐Sanchez et al, ). These prevalence rates are certainly a cause for concern and attention.…”
Section: Introductionsupporting
confidence: 89%
“…Ellis et al () found that 36% of their sample ( N = 363) were currently receiving harmful supervision. Similar findings have been reported in other studies, where prevalence rates vary between 20% and 40% (Bang & Goodyear, ; Ellis, ; Ellis, Creaner, Hutman, & Timulak, ; Hendricks & Cartwright, ; Nelson & Friedlander, ; Ramos‐Sanchez et al, ). These prevalence rates are certainly a cause for concern and attention.…”
Section: Introductionsupporting
confidence: 89%
“…In subsequent research, Ellis, Creaner, Hutman, and Timulak (2015) conducted a study of supervisees from a range of professions who worked in either the Republic of Ireland (RI) or the United States (US). In this cross-national study, the professional affiliations of both cohorts, Irish and American, were similar.…”
Section: Original Articlementioning
confidence: 99%
“…However, to date, no study has empirically examined how supervisees prioritize information for clinical supervision, including self‐identifying the needs of their clients and their own developmental needs. This question is salient given that many supervisees are operating autonomously with little to no direct observation from their supervisors (Ellis et al, , ; Rønnestad & Skovholt, ).…”
Section: Clinical Supervision For Licensurementioning
confidence: 99%
“…Despite the advantages of direct observation, prelicensed counselors often provide many clinical service hours with little or no direct oversight of their work by supervisors (Amerikaner & Rose, ; Ellis et al, ; Ellis, Creaner, Hutman, & Timulak, ). Furthermore, time in supervision is often limited as supervisors are only recommended to provide at least 1 hour of clinical supervision per week (Ellis et al, ).…”
mentioning
confidence: 99%